Utilization trends of drugs in patients admitted with ischemic heart disease in a tertiary care teaching hospital - Roy, Ayan; Biswal, Sashi Bhushan; Patel, Nayan Kumar; Hota, Prajit Saswat; Rath, Bhabagrahi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Coronary artery disease (CAD) takes the highest toll of lives across the world as well as India. Prompt diagnosis and effective treatment is lifesaving. Drug utilization studies scrutinize the appropriateness of treatment and provide favourable feedbacks to strengthen clinical practices. Several other studies have reported underuse of four evidence-based medicines namely aspirin, β-blockers, angiotensin-converting enzyme inhibitors (ACE-I) or angiotensin receptor blockers (ARB), and statins in patients with CAD. Polypharmacy, injection overuse is some of the shortcomings. The objectives of this study was to describe treatment practices in terms of different disease spectrum and drug utilization (group-wise and individually) for inpatients with CAD using core prescription indicators by WHO. Methods: A cross-sectional study of 4-month duration was undertaken for patients with CAD admitted to cardiology indoor of a tertiary care hospital. A total no of 143 prescriptions was screened and analyzed. Results: Males (67.13%) were more in number than females (32.87%). Age group from (57-66) topped in frequency (61.05%) ahead of (67 to 76) group (38.46%). Average no of drugs per patient were 8.056±1.97 and 5.86±0.14 for cardiovascular drugs. Prescription in generics (45.49%), antibiotics (0.61%), fixed-dose combinations (FDCs) (0.52%) and injectables (28.47%) were noted. The most common categories of CAD were ST-segment elevated myocardial infarction (69.23%) followed by chronic stable angina (17.48%). Antiplatelets (100%), hypolipidemics (99.3%), antianginals (60.14%), β-blockers (37.06%) and ACE-I/ARBs (27.97%) were utilized. Drugs from the national list of essential medicines were 66.49%. Conclusions: Among four evidence-based drugs, use of β-blockers and ACE-I/ARBs were inappropriately low. Polypharmacy and overuse of Injectable drugs are noted.